The effect of managerial Process Reengineering on organizational citizenship Applied research on Electronic Industries Company - علي شفاء محمد; زيا مروة بدر (Journal of Economics and Administrative Sciences, 2016)
ABSTRACT The research aims to know the reality of a two examined variables at the organization studied identifying the relationship between managerial processes reengineering and organizational citizenship behavior. The research applied on the Electronic Manufacturing Company encompassing a sample of managers and employees consisted of (100) individuals. A questionnaire is the main instrument for data gathering, which has been included (45) questions as well as personal interviews to support the questionnaire’s questions and to achieve greater realism for collecting information. Answers were analyzed to reach the final results through the use of a number of statistical methods via the statistical package (SPSS). The research has sought to test main hypotheses with the minor ones regarding correlation and regression relationships for answering questions that express the research problem, especially the basic question related with whether if there is some effect of managerial processes reengineering on the organizational citizenship behavior in the company studied? The research reached into some conclusions, the most important one is that there is a significant correlation and impact relationships between managerial processes reengineering and organizational citizenship behavior in the organization studied. Many commendations has also been reached, the most important ones are the notably increased reliance upon information technology for its vital role in minimizing lost time for operations through the provision of an electronic database that employees rely on their need to catch up with developments and stimulates them to do business more quickly and easily. Moreover, there is a need to develop educational courses and seminars for notifying employees about the importance of volunteerism and its benefits in addition to promote these behaviors through regulations and instructions necessary to reward the spontaneity and voluntarism efforts through various policies and human resources programs.